Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1037/fam0000852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual-oriented relationship education for parents: A randomized controlled trial.

Abstract: Individual-oriented relationship education aims to support healthy relationship development for singles, and provides flexibility for couples when only one member is available or willing to attend. While quasi-experimental studies have shown some benefits for those who attended relationship education individually, no randomized controlled trials have been conducted for individual-oriented RE. Moreover, it is not clear how relationship education benefits the co-parenting relationship when only one parent attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Rhoades and Stanley (2009), and Stanley et al (2020) discussed the practical benefits of providing relationship education to individuals, including the potential for fewer scheduling challenges, addressing sensitive topics that might not be appropriate or safe with both members of couple, and a focus on relationship development for those attendees not currently in a relationship. Previous studies have shown that providing relationship education to individuals can improve parenting and family relationships (Carlson et al, 2021), relationship conflict (Antle et al, 2011; Carlson et al, 2018; Patnaik & Wood, 2021); and relationship quality (Antle et al, 2013; Patnaik & Wood, 2021). Thus, there is support for more relationship education programs to target individual attendees.…”
Section: Implications For Relationship Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Rhoades and Stanley (2009), and Stanley et al (2020) discussed the practical benefits of providing relationship education to individuals, including the potential for fewer scheduling challenges, addressing sensitive topics that might not be appropriate or safe with both members of couple, and a focus on relationship development for those attendees not currently in a relationship. Previous studies have shown that providing relationship education to individuals can improve parenting and family relationships (Carlson et al, 2021), relationship conflict (Antle et al, 2011; Carlson et al, 2018; Patnaik & Wood, 2021); and relationship quality (Antle et al, 2013; Patnaik & Wood, 2021). Thus, there is support for more relationship education programs to target individual attendees.…”
Section: Implications For Relationship Educationmentioning
confidence: 99%
“…Limited research on individual-oriented relationship education programming exists. Researchers have found small positive effects on individual distress (Carlson et al, 2017), relationship quality (Visvanathan et al, 2015); conflict resolution (Antle et al, 2011;Carlson et al, 2018;Patnaik & Wood, 2021); communication (Antle et al, 2011); relationship skills and emotional well-being (Patnaik & Wood, 2021); and parenting/co-parenting (Carlson et al, 2021;Patnaik & Wood, 2021). Wadsworth et al (2011) randomly assigned participants to attend relationship education together as a couple or separately in an individual-oriented format.…”
Section: Individual-oriented Relationship Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta‐analyses demonstrate that relationship education with couples can be effective in improving relationship quality and communication skills (Hawkins et al, 2008; Hawkins & Erickson, 2015) and some studies with longer term follow‐up show that marriage education can prevent divorce (Stanley et al, 2014). Though less commonly studied, some studies also show impacts on parenting (Carlson et al, 2021; Le et al, 2021) and child (see review by Cowan & Cowan, 2014) outcomes, as well as individual mental health and physical health behaviors (Feinberg et al, 2010; Roddy et al, 2020).…”
mentioning
confidence: 99%